Comparison of recovery and enumeration of Escherichia coli, Cronobacter species, coliforms, and salmonella typhimurium in ground beef and ground turkey using conventional methods and a new chromogenic medium, ECA Check® Easygel® plus - Wenke, Erin Janet (Kansas State University, 2009)
ECA Check® Easygel® Plus (ECA) is a pectin-based gelling system that reacts with calcium ions bound to a pre-treated Petri dish, eliminating autoclaving prior to use. It can chromogenically and/or fluorogenically distinguish three organisms: Escherichia coli, Salmonella spp., and coliforms. This study compared the recovery of these organisms to conventional media using stock culture, inoculated, and non-inoculated ground beef and ground turkey. ECA was compared to Violet Red Bile Agar (VRB), Violet Red Bile Agar with 4-methylumbelliferyl-β-D-glucuronide (VRB-MUG), Xylose Lysine Desoxycholate Agar (XLD), Escherichia coli/Coliform (ECC) Count Plate Petrifilm™, and Tryptic Soy Agar (TSA). The stock culture recovery of Salmonella Typhimurium for ECA, TSA, and XLD were 8.62, 8.69, and 6.82 log CFU/ml, respectively. There was very little difference between the media in the recovery of Escherichia coli and Cronobacter spp., formerly referred to as Enterobacter sakazakii. Mean counts of presumptive E. coli in ground beef were 7.24 and 7.41 logs for ECA and VRB-MUG. Total coliform mean counts were 7.43, 7.63, and 7.37 logs for ECA, Petrifilm™, and VRB. Presumptive Salmonella means were 6.68 and 6.21 logs on ECA and XLD, while total aerobic counts were 7.84 and 6.51 logs on ECA and TSA. At 6.72 logs, ECA recovered considerably more Salmonella than XLD (5.71 logs) from the inoculated ground turkey; ECA recovered 7.62 logs total aerobic count which was significantly more than TSA at 6.89 logs. Total counts for both non-inoculated ground meats resulted in significant differences between TSA recovery and all other media. ECA also recovered significantly more than Petrifilm™ from both non-inoculated foods. The randomly selected organisms recovered from ECA were identified using BBL™ Crystal™ Enteric/Nonfermenter ID or Gram-Positive kits, and correlated precisely to the chromogenic reaction of the colonies. ECA Check® Easygel® was efficient, less labor-intensive, comparable to, and, in some instances, better than conventional media at recovering target organisms.
Keywords: Chromogenic media; Fluorogenic; Escherichia coli; Salmonella; Enterobacter sakazakii; Rapid methods pour plate; Agriculture, Food Science and Technology (0359)